Measuring value in the innovation processes of university-industry research centres. (26th April 2010) - Van Horne, Constance; Poulin, Diane; Frayret, Jean-Marc
There is increasing interest in new research relationships in the form of university-industry partnerships, by governments, universities, intermediary organisations and industry. These collaborations create value, however the value perceived, created and captured by the different actors in the innovation value network are different. However, based on the literature we can say that these values have to be present for all actors, at each phase, for the innovation process to continue. This paper presents a framework that illustrates a multi-actor view of the innovation process and associated values. It is hoped that this matrix can lead to new insight for researchers, practitioners and policy makers to manage better the innovation value network by facilitating the five phases of the innovation value network: policy making and grant process, idea generation and basic research, knowledge and technology development, knowledge and technology transfer and application of knowledge and technologies created by these research centres.